Component Based Software Development using Distributed Objects - E. Yedey, Sanjay (International Journal of Computer Sciences and Engineering, 2020)
The Object Oriented Programming paradigm has revolutionized the process of software development. It provides a great control over data and offers various revolutionary features like abstraction, encapsulation, polymorphism, inheritance that facilitates reusability of previous efforts done to build softwares. This approach makes it possible to develop softwares as reusable component that can be assembled with other. This software development paradigm makes it possible to develop software applications based on „plug and play‟ in which we can add, replace or modify components according to our needs. This Component Based Software development approach provides a cost effective, fast and modular approach for developing complex software with reduced delivery time. The technologies that facilitate Component development are distributed object technologies. The Distributed Object technology allows objects active in one process be accessed by another facilitating the computation be split over multiple processes. The processes involved may be running in different address spaces on single system or may be on different systems in a network in a local area network or the Internet. The most popular distributed object technologies are CORBA, RMI and DCOM. This paper presents an analysis of architecture and working of these technologies and compares software development methodology in these technologies on the basis of key terminologies used such as data marshalling, interoperability, heterogeneity, design transparency and speed.